2020
DOI: 10.1097/meg.0000000000001817
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and liver injury: a meta-analysis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 17 publications
7
74
2
2
Order By: Relevance
“… 16 18 Moreover, several studies found that SARS-CoV-2 infection was associated with abnormal liver enzymes and liver injury. 20 22 In the present study, we described LD among COVID-19 patients. LD was determined by measuring biochemical indexes, such as ALT, AST, DBIL and IBIL, several hepatocellular injury markers, total protein, albumin and globulin (three protein metabolic indexes), and ALP, TBA and γ-GGT (three markers of cholestasis).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“… 16 18 Moreover, several studies found that SARS-CoV-2 infection was associated with abnormal liver enzymes and liver injury. 20 22 In the present study, we described LD among COVID-19 patients. LD was determined by measuring biochemical indexes, such as ALT, AST, DBIL and IBIL, several hepatocellular injury markers, total protein, albumin and globulin (three protein metabolic indexes), and ALP, TBA and γ-GGT (three markers of cholestasis).…”
Section: Discussionmentioning
confidence: 84%
“…19 Liver injury was more popular in the critically ill COVID-19 patients with intensive care unit admission. 20 Nevertheless, the clinical characteristics of COVID-19-associated liver dysfunction (LD) are rarely described. The prognosis of LD of COVID-19 patients remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported a correlation between COVID-19 severity and LFT abnormalities, with elevated aminotransaminase levels being more frequent in ICU inpatients, and patients requiring ventilation (27)(28)(29). The pattern of liver injury is typically hepatocellular rather than cholestatic (30,31). The aspartate aminotransferase (AST) levels correlate highly with alanine aminotransferase (ALT) levels throughout the course of the illness suggesting a hepatocellular origin (32).…”
Section: Prevalence and Manifestations Of Liver Injury In Covid-19mentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a respiratory virus that primarily affects the lungs of the human host and that causes, in susceptible individuals, an unrestrained response of the immune system, respiratory failure, cardiovascular system damage, neuropsychiatric manifestations, and multiple organ injuries (1)(2)(3)(4). Since the first outbreak testimony in China at the end of the year 2019, the apparent disease termed coronavirus disease 2019 (COVID-19) had a large-scale spread within a few months.…”
Section: Introductionmentioning
confidence: 99%